Maternal Mortality in Indonesia, Ask for Help - Sutrisno Sutrisno, MD PhD OG (REI) (Asian Journal of Health Research, 2022)
Maternal mortality rate (MMR) consistently becomes a hot topic from day to day because there isn't a bright hope or the best exit door. Definition of maternal death according to World Health Organization (WHO) is the death of a woman while pregnant or within 42 days of termination of pregnancy, irrespective of the duration and site of the pregnancy, from any cause related to or aggravated by the pregnancy or its management but not from accidental or incidental causes. The amount of maternal death related to pregnancy has constantly been escalating from day to day since many decades ago. In the event of discussion at the Health Department of East Java Province in November ago, the data was alarming about a great problem related to maternal death in Indonesia.